Penyimpangan Sosial pada Lembaga Pendidikan - Sihaloho, Wardani; Dasopang, Masdeani; Handayani, Fitra; Sari, Nova; Sani, Fadilah (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
Research has been conducted to examine social deviations in PAUD institutions. One of the studies that influenced the occurrence of violence against children in PAUD institutions. In addition, there are also several regulations governing children's rights and child protection, such as Law Number 35 of 2014 concerning Child Protection and Regulation of the Minister of Education and Culture Number 137 of 2014 concerning National Standards for Early Childhood Education. Social deviations in PAUD institutions have very important relevance in the early childhood education industry. In the era of globalization and increasingly fierce competition, early childhood education is one of the key factors in forming a generation that is qualified and able to compete in the future. Therefore, maintaining the quality and integrity of PAUD institutions is very important. By dealing with social deviations in PAUD institutions, it is hoped that it can improve the quality of early childhood education and shape better children's character. In this study, literature studies were used to find sources of information and find scientific research. This approach examines theories that are appropriate to the topic, namely theories about the sociology of education. Deviations are categorized as procedures, methods, and practices that involve the release or action of measurements (rules) from the body. Individualized social organization is defined as everything related to society and community spirit, such as helping each other, donating, and so on. The term